Fraud prevention in village financial management an analysis of the regional inspectorate's role in Boyolali Regency - Sofi Wafda Fakhria; Zef Arfiansyah (PT WIM Solusi Prima, 2026)
Transparent village financial management is essential for good governance, yet fraud risks remain. This study examines the role of the Boyolali Regency Inspectorate in preventing fraud using the Three Lines Model. This qualitative case study collected data through interviews and document analysis. Findings reveal that the Inspectorate functions as an external supervisor ensuring accountability, though not part of the village’s internal structure. Given that primary oversight lies with the community and Village Consultative Body (BPD), the Three Lines Model is not fully applicable at the village level. To strengthen fraud prevention, the Inspectorate introduced innovations such as Auditor Pendamping, Jadi Kades, SAPU DESA, the Monitoring Center of Development, and cultural approaches, enhancing early detection and preventive control.